Practising academic mobilities: Bodies, networks and institutional rhythms. Issue 4 (24th May 2019) - Hopkins, Debbie; Higham, James; Orchiston, Caroline; Duncan, Tara
Abstract : Notions of what a successful academic should be doing – researching, publishing, teaching, serving the academic community – are often dependent upon particular practices of corporeal mobilities. These practices discursively and materially connect historically situated academic mobilities with the "modern, " globalised university system. At the same time, there is increasing attention being paid to the "hypocrisy of hypermobile academics" – often reliant on high‐carbon aeromobilities – in light of the unprecedented and urgent need to decarbonise transport to limit warming to 1.5°C. Using qualitative material gathered from one academic institution in Aotearoa New Zealand, we pay attention to the politics of academic mobilities at multiple scales, from the academic body, to social/family networks, and institutional rhythms. We contribute to the growing body of work that reflects on academic practice, and argue that detailed understandings of these processes are required to overcome the so‐called "climate hypocrisy" of high‐carbon academic work‐related travel.